Oxidative stress resistance of the yqhG mutant. - Jianhua Liao (1393228) (2025)
Log₁₀ CFU reductions in wild-type (WT), ΔyqhG, and complemented (ΔyqhG-C) strains after 20 min exposure to 1.5% hydrogen peroxide (H2O2) at 37 °C. Bacterial viability was assessed by serial dilution and CFU enumeration. Bars represent mean ± s.e.m. of three independent experiments. Statistical analysis was performed using one-way ANOVA. P < 0.05; ns, not significant.